EP1085 Surgical margins of large loop excision of the transformation zone: histological comparison with patient characteristics and colposcopists' experience. (1st November 2019) - Razvi, K; Rothnie, K; Speed, T; Clark, S
Abstract : Introduction/Background: Large loop excision of the transformation zone (LLETZ) is a standard procedure for the treatment of cervical intra-epithelial neoplasia (CIN). This audit aims to assess compliance with the NHS Cervical Screening Programme (NHSCSP) at Southend University Hospital, regarding recommended minimum excision depth of 7 mm and specimen removal as a single loop. The results were correlated to the experience of the colposcopist. Methodology: Retrospective audit identifying 224 patients who underwent LLETZ in 2015 from a colposcopy database. Patient age, colposcopist experience, margin involvement, depth excised, fragmentation, and recurrence at one year analysed. Patients were allocated to groups based on years of colposcopist experience - Group A (<5 years), Group B (5–10 years), Group C (>10 years). Results were compared to the NHSCSP guidelines. Results: Of the 224 patients, 51.79% (n=116) aged <35, and 19.64% (n=44) smokers. 26.34% (n=59) samples were from Group A, 51.34% (n=115) from Group B, and 22.32% (n=50) from Group C. The minimum depth of 7 mm achieved in 69.33% (n=156), with the highest rate in Group C (82.00%, n=41) - this is below the NHSCSP target of 95%. NHSCSP recommends an 80% target of specimens removed as a single loop. We achieved 72.77% (n=163), with the lowest proportion in Group A (66.10%, n=39). Group C met the target at 82.00%. Recurrence rate from the test of cure cytology was 15.11% (n=34). Conclusion: Our results are below NHSCSP standards. However, women in the younger age group may have less radical approaches to depth of excision in view of future fertility. The audit suggests years of experience affects the adequacy of LLETZ samples, with a higher rate of positive margins and specimens not removed as a single loop in Group A. The ability to obtain adequate LLETZ samples appears to be dependent on colposcopic experience. Disclosure: Nothing to disclose